Anthropogenic activities and the influence of desertification processes on the water cycle and water use in the Aral Sea basin - Alphonse Kayiranga; Xi Chen; Dative Ingabire; Tie Liu; Yaoming Li; Vincent Nzabarinda; Friday Uchenna Ochege; Hubert Hirwa; Eldiiar Duulatov; Winny Nthangeni (Journal of Hydrology: Regional Studies, 2024)
Study region: The Aral Sea Basin (ASB) is a transboundary water catchment area in Central Asia, with an area of around 1.8 million km2 and straddled over six countries namely Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan, Turkmenistan and Afghanistan. Study focus: This research investigated the associated controls of anthropogenic activities and desertification process on the water cycle in the ASB, produced long-term spatial maps, quantified and evaluated the changes in the water surface, volume and water level of the Aral Sea Lake, agricultural water yield and water use efficiency based on multiple streams of state-of-art high-resolution imageries, reanalyzed and in-situ observations during 1986–2022. New hydrological insights for the region: The main findings of this research are as follows: (i) The Aral Sea Lake was characterized by sharp decline trends in the water surface area, volume and water level with the annual decreasing rates of approximately 1.02 × 103 km2.yr−1, 9.59 km3.yr−1 and 1.14 m. yr−1, respectively; (ii) Agricultural water yield indicated an overall annual decreasing rate of 0.45 mm. yr−1; (iii) Based on the imbalance between agricultural water demand and water supply, these results showed that the ASB has an annual water deficit for agricultural irrigation of approximately 0.071 km3.yr−1 and this water deficit has significantly affected wheat production in Kyrgyzstan and slightly in Afghanistan and Turkmenistan. (iv) The assessment of water threats shows that anthropogenic activities strongly influence the water cycle in the ASB compared to the factors of the desertification process. These results are of great importance and have significant implications for decision makers for future ecohydrological studies and water management in Central Asia and other hotspots of the global drylands.